Core-in-cup/liquisol dual tackling effect on azelnidipine buccoadhesive tablet micromeritics, in vitro release, and mucoadhesive strength - Rashad Amira A.; El-Helaly Sara Nageeb; Abd El Rehim Randa T.; El-Gazayerly Omaima N. (Acta Pharmaceutica)
Reduced bioavailability of azelnidipine is related to its poor aqueous solubility and extensive first-pass metabolism, which hinder its efficacy. These problems were addressed by implementing (1) a liquisol technique for promoting the dissolution rate in a controlled-release manner and (2) a core-in-cup bucco-adhesive drug delivery system as an alternative to the oral route. A 33 factorial design was used to study the effects of polymer type (sodium carboxymethyl cellulose (CMC Na), chitosan, or Carbomer P940) concentration (5, 10 or 15 %) and preparation technique (simple mix, liquisol or wet granulation) on the dissolution and mucoadhesion of core-in-cup azelnidipine buccoadhesive tablets. Tablet micromeritics, swelling index, mucoadhesive strength and in vitro release were characterized. Statistical analyses of these factors show ed significant effects on the studied responses, where F#16 prepared by the liquisol technique and containing 15 % CMC Na was chosen with an overall desirability of 0.953.